PENERAPAN PENDEKATAN VISUAL DALAM PEMBELAJARAN MENULIS HURUF MELALUI IMAJINASI PADA ANAK PAUD KARTINI, TANJUNG MORAWA - Aldino; Nurmayani; Maya Alemina Ketaren; Mikael Angelo Sitanggang; Susilo Jordan Situmorang (Jurnal Genta Mulia, 2025)
This study aims to examine the effectiveness of an imagination-based visual approach in letter-writing instruction for early childhood students at PAUD Kartini, Tanjung Morawa. The background of this study stems from the fact that children experience difficulties in writing letters due to monotonous teaching methods that do not align with their fine motor and cognitive developmental stages. This research employed a descriptive qualitative method using observation and documentation to collect data on children's letter-writing abilities before and after the implementation of the visual approach. The results indicate a significant improvement in children's letter-writing skills after applying the imagination-based visual method. Previously abstract letters became more meaningful and recognizable through associations with familiar real-world objects. These findings suggest that the visual approach can be an innovative alternative for enjoyable and contextual letter-writing instruction.